2002
DOI: 10.1002/ajh.10230
|View full text |Cite
|
Sign up to set email alerts
|

Novel nonsense mutation in the platelet glycoprotein Ibβ gene associated with Bernard‐Soulier syndrome

Abstract: Bernard-Soulier syndrome (BSS) is an autosomal recessive bleeding disorder caused by quantitative or qualitative abnormalities in the glycoprotein (GP) Ib/IX/V complex, the platelet receptor for von Willebrand factor. This complex is composed of four subunits, GPIb␣, GPIb␤, GPIX, and GPV, and the coordinated assembly of GPIb␣, GPIb␤, and GPIX is required for the efficient surface expression of a functional complex. We report here a novel nonsense mutation of the GPIb␤ gene associated with BSS. Flow cytometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Several of the GP Ib␤ gene mutations that have been described are missense mutations. 23,[28][29][30] In general, these mutations might be expected to have a minimal effect on transcript stability. However, in the case of Watanabe et al, 8 who observed abnormal vesicles, the mutation is a 13-bp deletion within the signal peptide coding region of the GP Ib␤ gene.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the GP Ib␤ gene mutations that have been described are missense mutations. 23,[28][29][30] In general, these mutations might be expected to have a minimal effect on transcript stability. However, in the case of Watanabe et al, 8 who observed abnormal vesicles, the mutation is a 13-bp deletion within the signal peptide coding region of the GP Ib␤ gene.…”
Section: Discussionmentioning
confidence: 99%
“…40 Some are frameshifting or nonsense mutations, resulting in a typically truncated and nonfunctional protein product. [41][42][43] In this study, we have for the first time systematically characterized all the reported missense BSS mutations in GPIb␤ and observed distinct mechanisms that underlie the pathogenesis of the disease (Figure 2). Six of the 8 missense mutations are detrimental to proper tertiary folding or secretion of GPIb␤ E .…”
Section: Different Pathways To Bssmentioning
confidence: 95%
“…It is not evident, however, whether the Ib␤ TM domain is as important as its counterparts in GP Ib␣ and IX. No mutations within the Ib␤ TM domain have been reported to prevent surface expression of the receptor complex, although a nonsense mutation effectively removing the entire TM and cytoplasmic domains of GP Ib␤ has (20).…”
Section: Lack Of Expression Of Glycoprotein (Gp)mentioning
confidence: 99%